MANAJEMEN PENGELOLAAN SARANA DAN PRASARANA DI MI TAHFIZ ANWARUL HASANIYYAH - Awaliatul Najiah; Herni Herni; Indah Suci; Syahrani Syahrani (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
Management of facilities and infrastructure is very important because by managing the facilities and infrastructure of educational institutions, their use will be maintained and clear. In managing the school, the school must be responsible for the facilities and infrastructure, especially the school principal who directly handles the facilities and infrastructure. And the school must be able to maintain and pay attention to existing school facilities and infrastructure. So, with the facilities and infrastructure at school, students can learn optimally and as efficiently as possible. So the management of facilities and infrastructure must be emphasized more in educational institutions such as schools. By managing existing facilities and infrastructure at the school, the principal can plan and record what facilities and infrastructure should be used at the school. If all management steps have gone well as expected, it will have a positive impact on students in the teaching and learning process and achieving educational goals effectively and efficiently. The method used is quantitative research in the form of frequency distribution.